2015
DOI: 10.9734/ajea/2015/20577
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Diversity of Selected Dual Purpose Forage and Grain Sorghum Genotypes

Abstract: Aims: To study the phenotypic diversity of 25 forage and 45 grain sorghum genotypes for dual purpose as food and feed and to identify traits that might contribute to genetic improvement. Study Design: A 7 × 10 alpha lattice design was used with two replications at two sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 16 publications
2
13
0
Order By: Relevance
“…The phenotypic expression could be influenced by rainfall and temperature difference between the seasons as recorded with 522 mm during 2016 and 989 mm in 2017. Similar findings from Chikuta et al (2015) and Ayana et al (2000) indicate that gradient of rainfall, temperature and growing sites are important for genotype variation. The phenotypic expression can infer genetic variability and consequences of phenotypic variation due to changes in the environment (Abubakar and Bubuche, 2013).…”
Section: Variability and Heritability Of The Characterssupporting
confidence: 66%
See 2 more Smart Citations
“…The phenotypic expression could be influenced by rainfall and temperature difference between the seasons as recorded with 522 mm during 2016 and 989 mm in 2017. Similar findings from Chikuta et al (2015) and Ayana et al (2000) indicate that gradient of rainfall, temperature and growing sites are important for genotype variation. The phenotypic expression can infer genetic variability and consequences of phenotypic variation due to changes in the environment (Abubakar and Bubuche, 2013).…”
Section: Variability and Heritability Of The Characterssupporting
confidence: 66%
“…These methods use the morphological characters to provide information about the similar groups and the information generated can be used to identify genotypes that have desirable characters for breeding purposes such as hybridization for pedigree breeding. Chikuta et al (2015) used multivariate analysis approaches to select sorghum genotypes exhibiting high levels of grain and fodder traits from morphological and agronomic data, while Mujaju and Chakauya (2008) used multivariate analysis to categorise agro-morphological characters of sorghum landraces to explain production factors and uses of sorghum at farmers' level.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ayana and Bekele (1999) reported significance of first five PCs in the total variability of different agro-morphological traits in sorghum. The first four principal components, with eigenvalues greater than one, were also documented in 25 forage and 45 grain sorghum genotypes for dual purpose (Chikuta et al 2015). Abraha et al (2015) reported four principal components with eigenvalues greater than one, which explained > 75% of the total variation for grain yield, biomass, stay-green, leaf area, peduncle exertion, days to flowering, and maturity.…”
Section: Resultsmentioning
confidence: 85%
“…‡ ‡ = Awned glume (1 = awned glume panicles and 2 = non-awned glume panicles). attributed to first, second, and third principal components, respectively, was reported by Chikuta et al (2015). Several studies on principal component analysis of different agro-morphological traits in sorghum have been documented.…”
Section: Resultsmentioning
confidence: 88%